PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR IPAS MATERI PERUBAHAN WUJUD BENDA KELAS V SDK SANTO YOSEPH 4 NAIKOTEN - Jepson Mandala; Yulsy M Nitte; Heryon B Mbuik (STKIP Subang, 2026)
Mandala, Jepson. 2026. The Effect of Guided Inquiry Learning Model on Science Learning Outcomes on Changes in the State of Matter of Fifth Grade Students of SDK Santo Yoseph 4 Naikoten. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University. Supervisor I: Yulsy Marselina Nitte, S.H., M.Pd.; Supervisor II: Heryon Bernard Mbuik, S.PAK., M.Pd. This research is motivated by the low science learning outcomes of fifth grade students of SDK Santo Yoseph 4 Naikoten on changes in the state of matter, which is caused by the learning that is still dominated by lecture methods, resulting in students being less active in the learning process. This study aims to determine the effect of the guided inquiry learning model on students' science learning outcomes-. The study used a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The study population was 24 fifth grade students of SDK Santo Yoseph 4 Naikoten, all of whom were sampled using a saturated sampling technique, then divided into an experimental class and a control class. The data collection technique used learning outcome tests and documentation. Data were analyzed through normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that the average posttest score for the control class was 63.33, while the average posttest score for the experimental class was 85.42. The results of the hypothesis test indicated a significant difference between the learning outcomes of the two classes, indicating that the guided inquiry learning model had a positive effect on the science learning outcomes of fifth-grade students of SDK Santo Yoseph 4 Naikoten on the topic of changes in the state of matter. Therefore, it can be concluded that the application of the guided inquiry learning model is effective in improving the learning outcomes of fifth-grade students of SDK Santo Yoseph 4 Naikoten.